2011
DOI: 10.2478/s11756-011-0131-1
|View full text |Cite
|
Sign up to set email alerts
|

Anaplasma phagocytophilum and other tick-borne bacteria in wild animals in western Slovakia

Abstract: Tick-borne bacterial zoonoses of livestock and free-ranging ungulates caused by Anaplasma spp. are common in Central Europe. The aim of this study was to analyze the prevalence of Anaplasma phagocytophilum and other tick-borne bacteria in wild animals from western Slovakia. Infection with A. phagocytophilum was recorded in 62.86% of analyzed roe deer (Capreolus capreolus), in two red deer (Cervus elaphus) and two wild boars (Sus scrofa). Dermacentor reticulatus and Ixodes ricinus ticks collected on red deer we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 21 publications
(20 reference statements)
0
2
1
Order By: Relevance
“…The presence of this bacterium in game has frequently been reported from different regions of Europe [ 19 , 95 ], with varying prevalences depending on the host species, examined tissue, site, but also on the sensitivity of the detection method used. The infection rates of 100% in red deer, 95.4% in fallow deer, and 92.9% in roe deer estimated from our study are higher than values previously reported from Slovakia: red deer 17.5–53.1% [ 24 , 57 , 102 ]; fallow deer 66.7% [ 24 ], and roe deer 50–77% [ 24 , 57 , 102 , 103 ]. The infection rates determined in this study are in the upper range of those confirmed by PCR in cervids from other countries of mainland Europe, where the values in red deer ranged between 1.5–86% [ 89 , 104 114 ], in fallow deer between 1.5–72.5% [ 42 , 105 , 106 , 108 , 110 , 112 , 115 , 116 ] and in roe deer between 9.6–98.9% [ 38 , 42 , 89 , 105 – 113 , 117 120 ].…”
Section: Discussioncontrasting
confidence: 72%
“…The presence of this bacterium in game has frequently been reported from different regions of Europe [ 19 , 95 ], with varying prevalences depending on the host species, examined tissue, site, but also on the sensitivity of the detection method used. The infection rates of 100% in red deer, 95.4% in fallow deer, and 92.9% in roe deer estimated from our study are higher than values previously reported from Slovakia: red deer 17.5–53.1% [ 24 , 57 , 102 ]; fallow deer 66.7% [ 24 ], and roe deer 50–77% [ 24 , 57 , 102 , 103 ]. The infection rates determined in this study are in the upper range of those confirmed by PCR in cervids from other countries of mainland Europe, where the values in red deer ranged between 1.5–86% [ 89 , 104 114 ], in fallow deer between 1.5–72.5% [ 42 , 105 , 106 , 108 , 110 , 112 , 115 , 116 ] and in roe deer between 9.6–98.9% [ 38 , 42 , 89 , 105 – 113 , 117 120 ].…”
Section: Discussioncontrasting
confidence: 72%
“…Unlike in the USA, A. phagocytophilum genotypes that are associated with European rodents are probably transmitted solely by I. trianguliceps, therefore these strains may be not of risk for humans, considering the narrow host selection behaviour and feeding preference of this tick species (Blaňarová et al 2014). The main reservoir hosts for A. phagocytophilum in Slovakia are wild living ungulates (Smetanová et al 2006;Stefanidesova et al 2008;Štefanidesová et al 2011;Víchová et al 2014;Kazimírová et al 2018) (Table 2). Kazimírová et al (2018) reported very high prevalence of A. phagocytophilum in cervids from SW Slovakia where locally 100% of red deer, 95.4% of fallow deer and 92.9% of roe deer were infected.…”
Section: Anaplasma Phagocytophilummentioning
confidence: 99%
“… Trávniček et al (2003) ; Bhide et al (2004) Capreolus capreolus , Cervus elaphus , Ovis musimon Anaplasma phagocytophilum Stefanidesova et al (2008) Capreolus capreolus , Cervus elaphus , Sus scrofa Anaplasma phagocytophilum Smetanová et al (2006) ; Štefanidesová et al (2016) Capreolus capreolus Anaplasma phagocytophilum ✓ (deer ked Lipoptena cervi ) Víchová er al. (2011) Capreolus capreolus , Cervus elaphus , Dama dama , Sus scrofa Anaplasma phagocytophilum Víchová et al (2014) Capreolus capreolus Rickettsia helvetica Stefanidesova et al (2008) Sus scrofa Anaplasma phagocytophilum Štefanidesová et al (2011) Sus scrofa Anaplasma phagocytophilum Reiterová et al (2016) Sus scrofa Rickettsia helvetica Nováková et al (2022) Ovis aries musimon , D. dama TBEV, Borrelia ,...…”
Section: Tick Borne Pathogens Vectors Reservoir Hosts and Knowledge Gapsmentioning
confidence: 99%